2023
DOI: 10.1371/journal.pone.0283147
|View full text |Cite
|
Sign up to set email alerts
|

Comparative metabolomics analysis reveals alkaloid repertoires in young and mature Mitragyna speciosa (Korth.) Havil. Leaves

Abstract: The fresh leaves of Mitragyna speciosa (Korth.) Havil. have been traditionally consumed for centuries in Southeast Asia for its healing properties. Although the alkaloids of M. speciosa have been studied since the 1920s, comparative and systematic studies of metabolite composition based on different leaf maturity levels are still lacking. This study assessed the secondary metabolite composition in two different leaf stages (young and mature) of M. speciosa, using an untargeted liquid chromatography-electrospra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 106 publications
(163 reference statements)
0
2
0
Order By: Relevance
“…Only six alkaloids were found at higher levels in RS than in SD, including L-tyramine, trigonelline, and dhurrin (Figure S7). These results indicate that SD is richer in medicinally beneficial alkaloids that have outstanding biological activities [64]. We also found an interesting phenomenon in which the levels of most terpenoids in CV were significantly higher than those in RS and SD (Figure S8).…”
Section: Discussionmentioning
confidence: 59%
“…Only six alkaloids were found at higher levels in RS than in SD, including L-tyramine, trigonelline, and dhurrin (Figure S7). These results indicate that SD is richer in medicinally beneficial alkaloids that have outstanding biological activities [64]. We also found an interesting phenomenon in which the levels of most terpenoids in CV were significantly higher than those in RS and SD (Figure S8).…”
Section: Discussionmentioning
confidence: 59%
“…While such findings support the notion that the ingredients of different kratom products can vary substantially, thus far no empirical research has explored whether kratom products sold as different strains are reliably associated with distinct effect profiles. One phytochemical study did examine the metabolomic profile of young and mature kratom leaves and identified five unique alkaloids between the young and mature leaves while 76 secondary metabolites were present in both leaf samples, albeit in different concentrations [18]. While the major alkaloid mitragynine is present in approximately equal amounts in both young and mature leaves, some of the other indole alkaloids, including speciogynine, speciociliatine, and 7-hyroxymitragynine, are present in higher abundance in mature leaves.…”
Section: Introductionmentioning
confidence: 99%